( | x | + | 4 | ) | ÷ | 3 | + | ( | x | − | 3 | ) | ÷ | 4 | = | 4 | ÷ | 3 |
Left side of the equation = | x | × | 1 3 | + | 4 | × | 1 3 | + | ( | x | − | 3 | ) | × | 1 4 |
= | x | × | 1 3 | + | 4 3 | + | ( | x | − | 3 | ) | × | 1 4 |
= | 1 3 | x | + | 4 3 | + | x | × | 1 4 | − | 3 | × | 1 4 |
= | 1 3 | x | + | 4 3 | + | x | × | 1 4 | − | 3 4 |
= | 7 12 | x | + | 7 12 |
7 12 | x | + | 7 12 | = | 4 | ÷ | 3 |
Right side of the equation = | 4 3 |
7 12 | x | + | 7 12 | = | 4 3 |
7 12 | x | = | 4 3 | − | 7 12 |
7 12 | x | = | 3 4 |
x | = | 3 4 | ÷ | 7 12 |
= | 3 4 | × | 12 7 |
= | 3 | × | 3 7 |
x | = | 9 7 |
x | = | 1.285714 |